VO#033 Extra works for water treatment plant system rev.0 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of proposal of cost amount against extra works for water treatment plant system that includes plant supply, transportation, installation etc. for BRACU new campus project.